(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article is devoted to the analysis of the evolution of some religions and religious movements and their influence on policy in the history of mankind. As well as, article based outlines the history of the formation within the religious freedom and religious tolerance. Specifies the leading role of religious tolerance and religious faith in state life, as one indicator of the stability and development of the state. In Article is carried out a retrospective analysis, are given a lot of factorial and descriptive examples of how and what policies adhered King Cyrus respect for religious freedom that be increase, strengthening of the him state, about role of religion in state policy of Genghis Khan, about religious freedom, the position of religions in the political history of France, UK, USA and other countries. The purpose of the article to find answers to questions related to the following notions: religion and policy, human freedom and freedom of religion, human and his constitutional rights, what should be the policy of the state in the sphere of religion and etc. Key words: Religion, government, politics, political will, religious freedom, religious tolerance, state security, constitution.